Strategi Manajemen Pariwisata Berbasis Masyarakat dalam upaya Pemberdayaan Ekonomi Lokal di Desa Wisata Kubu Gadang Provinsi Sumatera Barat - Rahmad Ramadan; Fernando Fasandra; Naufal Hibatullah (Jurnal Projemen UNIPA, 2025)
Community-Based Tourism is an approach to tourism development that involves the active participation of local communities as the main actors in planning, managing, and utilizing tourism business results. This study aims to examine effective management strategies in managing community-based tourism to encourage local economic empowerment. The research method uses a descriptive qualitative study with a case study approach in Kubu Gadang Tourism Village, West Sumatra Province. Data were collected through observation, documentation, and interviews. The results of the study indicate that management strategies involving community capacity training, clear role divisions, and collaboration with external parties (government and private sector) are able to increase community income and strengthen the village economic structure. The implications of this study indicate that good management is the key to the success of community-based tourism in creating inclusive and sustainable economic development.